KOMUNIKASI INTERPERSONAL ORANGTUA DAN ANAK DALAM MEMBANGUN MOTIVASI BELAJAR SISWA SMP NEGERI 4 KANDIS KELURAHAN KANDIS KOTA KECAMATAN KANDIS KABUPATEN SIAK RIAU - ', Dilvera; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
SMPN 4 Kandis is one of the favorite junior high schools in Kandis Kota Village, but in the last 5 years there have been no school achievements recorded, and many students do not reach the minimum score assessment/KKM. Students' lack of motivation to learn is a factor in this problem. In the learning process, motivation and enthusiasm are very important things that children need to have. Interpersonal communication between parents and children is needed in order to build learning motivation. This study aims to analyze the how the aspects of interpersonal communication between parents dand children in building student learning motivation and to understand what are the inhibiting factors of interpersonal communication between parents and children in increasing student learning motivation at SMPN 4 Kandis. This research used descriptive qualitative methods, with twelve research subjects selected using purposive techniques. Data collection techniques were interviews, non-participant observation, and documentation studies. The data analysis technique used was Miles & Huberman's interactive model, namely data reduction, data presentation, and conclusion drawing. Data validity checking techniques are extension of participation and triangulation. The results showed that interpersonal communication between parents and children is key to building learning motivation through the application of interpersonal communication aspects, namely openness, empathy, support, a positive attitude, and equality. Children with parents who apply aspects of interpersonal communication tend to have children with high learning motivation and good learning achievement, and vice versa. The inhibiting factors of parents' interpersonal communication in building children's learning motivation are internal factors such as laziness as well as external factors such as socialization and excessive use of gadgets. Keywords : Interpersonal Comunication, Comunication of Parents and Children, Learning Motivation